BambooMC — A Geant4-based simulation program for the PandaX experiments. (21st September 2021) - Chen, X.; Cheng, C.; Fu, M.; Giuliani, F.; Liu, J.; Lu, X.; Ji, X.; Qian, Z.; Qiao, H.; Wang, Q.; Xia, J.; Xie, P.; et al.
Abstract: The purpose of the PandaX experiments is to search for the possible events resulted from dark matter particles, neutrinoless double beta decay or other rare processes with xenon detectors. Understanding the energy depositions from backgrounds or calibration sources in these detectors is very important. The program of BambooMC is created to perform the Geant4-based Monte Carlo simulation, providing reference information for the experiments. We introduce the design and features of BambooMC in this report. The running of the program depends on a configuration file, which combines different detectors, event generators, physics lists and analysis packs together in one simulation. The program can be easily extended and applied to other experiments.